Olfactory Perception and Presence in a Virtual Reality Food Environment - Persky, Susan; Dolwick, Alexander P. (Frontiers in Virtual Reality, 2020)
Virtual reality (VR)'s effectiveness as a medium for training, education, research, and entertainment, is based in large part on the fact that users can be deeply immersed and feel present within virtual environments. Olfaction has received less attention regarding its ability to add realism to VR environments. It is important to investigate under which circumstances olfactory stimuli are likely to add to user experience and help achieve the goals of VR applications. This study examined the role of scent in a VR-based buffet restaurant environment. French fry scented oil was administered while participants made a plate of food in the VR Buffet. Participants were asked afterwards to report on smells they perceived. Only 18% of participants perceived the olfactory stimulus, 78% of whom correctly identified it. Perceiving the olfactory stimulus was associated with higher levels of presence in the VR Buffet. Correctly identifying the olfactory stimulus was associated with heightened presence and increased likelihood of choosing french fries from the VR Buffet. These results demonstrate the potential for variability in scent perception and related user experience in VR. Additionally, this study highlights a need for future research into factors that underlie and moderate olfactory perception in VR environments.